A Study on the Potential Vulnerability of Debris Flow Hazard in Sukabumi Regency - Nur Aliyah; Supriatna; A Azis Kurniawan (http://arl.faperta.ipb.ac.id/, 2022)
Debris-flow hazards are a hydrometeorological disaster that often occurs in parts of Indonesia. The intensity of Debris-flow hazards increases Debris-flow hazards are a Debris-flow Debris-flow hazards are a hydrometeorological disaster that often occurs in parts of Indonesia. The intensity of Debris-flow hazards increases in various parts of Indonesia in line with climate change and environmental degradation. Sukabumi Regency has a diverse topography with a relatively high annual rainfall rate of 2,805 mm/year with 144 rainy days. In 2020, Sukabumi Regency was affected by Debris-flow hazards in three Districts. In a study by the National Disaster Management Agency (BNPB), Sukabumi District is prone to land movements. There has been no study of Debris-flow hazards in the Sukabumi Regency area. This study aims to determine regions of the Sukabumi Regency that have the potential for Debris-flow hazards. It is hoped that the study results will also complement the disaster studies that BNPB has made. The method used is a weighted multi-criteria analysis. The parameters used are rainfall, location of the 2020 flood, slope, land cover, altitude, and soil type. The results showed that the level of vulnerability is very prone to be located in the northern part of Sukabumi.